2010
DOI: 10.5483/bmbrep.2010.43.8.530
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CYP1A2 gene polymorphisms on Theophylline metabolism and chronic obstructive pulmonary disease in Turkish patients

Abstract: Cytochrome P450 (CYP) 1A2 gene polymorphisms are thought to be involved in the metabolism of theophylline (TP). We aimed to investigate the effect of CYP1A2*1C, CYP1A2*1D, CYP1A2*1E, and CYP1A2*1F polymorphisms of the CYP1A2 on TP metabolism by PCR-RFLP in 100 Turkish patients with chronic obstructive pulmonary disease (COPD) receiving TP. One hundred and one healthy volunteers were included as control group. The genotype frequencies of the CYP1A2*1D and CYP1A2*1F were found to be significantly different in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 18 publications
0
10
0
5
Order By: Relevance
“… found CYP1A2*1C polymorphism was associated with reduced theophylline clearance in Japanese asthma patients (non‐smokers), and Uslu et al . reported that CYP1A2*1D and CYP1A2*1F were significantly associated with altered theophylline concentration in Turkish patients. Because both frequency spectrums of SNPs and haplotype structures at CYP1A2 are different between different ethnics, these results were not contradictory to ours.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… found CYP1A2*1C polymorphism was associated with reduced theophylline clearance in Japanese asthma patients (non‐smokers), and Uslu et al . reported that CYP1A2*1D and CYP1A2*1F were significantly associated with altered theophylline concentration in Turkish patients. Because both frequency spectrums of SNPs and haplotype structures at CYP1A2 are different between different ethnics, these results were not contradictory to ours.…”
Section: Discussionmentioning
confidence: 97%
“…Uslu A et al . reported that CYP1A2*1D was significantly associated with theophylline metabolism in Turkish patients . However, another study in Japanese patients reported that there was no influence of CYP1A2*1C and CYP1A2*1F on the theophylline metabolic ratio .…”
mentioning
confidence: 96%
“…14,15 Oleh karena itu, diperlukan penelitian yang lebih lanjut mengenai farmakogenomik untuk mengetahui efek obat yang dipengaruhi oleh genetik karena respons obat dapat ditentukan oleh hubungan antara genotipe. [16][17][18][19] Beberapa studi terdahulu terhadap ras yang berbeda telah menunjukkan bahwa efek polimorfisme gen CYP1A2 memengaruhi metabolisme teofilin pada pasien asma yang menggunakan teofilin atau aminofilin sebelumnya sehingga akan memengaruhi kadar teofilin dalam darah. 17,18 Hal ini dapat memengaruhi keamanan obat tersebut dan risiko terhadap terjadinya ADR.…”
Section: Pendahuluanunclassified
“…[16][17][18][19] Beberapa studi terdahulu terhadap ras yang berbeda telah menunjukkan bahwa efek polimorfisme gen CYP1A2 memengaruhi metabolisme teofilin pada pasien asma yang menggunakan teofilin atau aminofilin sebelumnya sehingga akan memengaruhi kadar teofilin dalam darah. 17,18 Hal ini dapat memengaruhi keamanan obat tersebut dan risiko terhadap terjadinya ADR. Identifikasi dan karakterisasi sejumlah besar polimorfisme genetik (biomarker) dalam enzim metabolisme obat dan transporter obat dalam etnis berbagai kelompok individu dapat memberikan pengetahuan substansial tentang mekanisme antarindividu dalam menanggapi obat.…”
Section: Pendahuluanunclassified
“…Показано, что клиренс теофиллина достоверно меньше у носителей аллельного варианта G2964A CYP1A2, с генотипами GA или АА, ассоциированными с медленной скоростью метаболизма лекарственных средств-субстратов [6,10]. Доказано влияние полиморфизма гена CYP1A2 на метаболизм теофиллина и формирование хронической обструктивной болезни лёгких [13,14] При изучении равновесного распределения частот изучаемых генотипов по полиморфному маркёру было установлено, что группа исследования (n=250) соответствует равновесию Харди-Вайнберга (p >0,05). Это позволяет сделать вывод о репрезентативности выборки и достоверности полученных результатов.…”
Section: генетические предикторы эффективности и безопасности теофиллunclassified